Truth and Clarity in Teaching and Education - Stein, Edyta; Bogaczyk-Vormayr, Małgorzata (Paedagogia Christiana, 2026)
Truth and Clarity in Teaching and Education (Wahrheit und Klarheit im Unterricht und in der Erziehung) was Edith Stein’s first public lecture, delivered on the 11th September 1926 at the Annual Pedagogical Conference in Speyer (Bavaria), where she lived and taught at the time – at the Dominican Pedagogical Institute (Lehrerinnenbildungsanstalt der Dominikanerinnen, St. Magdalena). The 1920s and early 1930s were the most important period of her research in the field of education theory, a time of her own intensive teaching activity (she gave lectures and courses mainly for teachers). From these years came most of the manuscripts – a small number of which were published during her lifetime – that made up the 16th volume of Edith Stein Collected Works (ESGA, Herder Verlag). The Polish translation is based on this edition.